A PWWP Domain-Containing Protein Targets the NuA3 Acetyltransferase Complex via Histone H3 Lysine 36 trimethylation to Coordinate Transcriptional Elongation at Coding Regions - Gilbert, Tonya M. (Mol Cell Proteomics, 2014)
Post-translational modifications of histones, such as acetylation and methylation, are differentially positioned in chromatin with respect to gene organization. For example, although histone H3 is often trimethylated on lysine 4 (H3K4me3) and acetylated on lysine 14 (H3K14ac) at active promoter regions, histone H3 lysine 36 trimethylation (H3K36me3) occurs throughout the open reading frames of transcriptionally active genes. The conserved yeast histone acetyltransferase complex, NuA3, specifically binds H3K4me3 through a plant homeodomain (PHD) finger in the Yng1 subunit, and subsequently catalyzes the acetylation of H3K14 through the histone acetyltransferase domain of Sas3, leading to transcription initiation at a subset of genes. We previously found that Ylr455w (Pdp3), an uncharacterized proline-tryptophan-tryptophan-proline (PWWP) domain-containing protein, copurifies with stable members of NuA3. Here, we employ mass-spectrometric analysis of affinity purified Pdp3, biophysical binding assays, and genetic analyses to classify NuA3 into two functionally distinct forms: NuA3a and NuA3b. Although NuA3a uses the PHD finger of Yng1 to interact with H3K4me3 at the 5′-end of open reading frames, NuA3b contains the unique member, Pdp3, which regulates an interaction between NuA3b and H3K36me3 at the transcribed regions of genes through its PWWP domain. We find that deletion of PDP3 decreases NuA3-directed transcription and results in growth defects when combined with transcription elongation mutants, suggesting NuA3b acts as a positive elongation factor. Finally, we determine that NuA3a, but not NuA3b, is synthetically lethal in combination with a deletion of the histone acetyltransferase GCN5, indicating NuA3b has a specialized role at coding regions that is independent of Gcn5 activity. Collectively, these studies define a new form of the NuA3 complex that associates with H3K36me3 to effect transcriptional elongation. MS data are available via ProteomeXchange with identifier PXD001156.